Preliminary evidence linking complex-PTSD to insomnia in a sample of Yazidi genocide survivors. (January 2019) - Grossman, Ephraim S.; Hoffman, Yaakov S.G.; Shrira, Amit; Kedar, Mordechai; Ben-Ezra, Menachem; Dinnayi, Mirza; Zivotofsky, Ari Z.
Highlights: Hitherto insomnia prevalence in complex-PTSD has not been examined. We examined insomnia in a group of 108 Yazidi genocide survivors. Results show that complex-PTSD and insomnia almost completely overlapped. Insomnia prevalence in complex-PTSD was much higher than all other groups. Complex-PTSD was associated with insomnia beyond PTSD effects. Abstract: Complex post-traumatic stress disorder (CPTSD) is a psychiatric diagnosis that includes three additional symptom clusters beyond those necessary for post-traumatic stress disorder (PTSD) diagnosis. CPTSD is typically associated with a prolonged trauma exposure in which a person's destiny is under the control of other people and escape is not an option. Insomnia prevalence in women suffering from CPTSD was compared to the prevalence of insomnia in those with no-PTSD and those with only PTSD. Yazidi women ( N  = 108, age = 24.41 ± 5.71) former captives of the Islamic State terrorist group were queried about captivity variables, psychological distress, resilience, PTSD, CPTSD, and insomnia. CPTSD prevalence was high (>50%) and was highly correlated with insomnia (95% of those with CPTSD had insomnia). A dichotomous insomnia variable was regressed on age and marital-status (Step 1), captivity-duration and number of fellow captives (Step 2), resilience and psychological distress (Step 3), and group (no-PTSD/PTSD/CPTSD) (Step 4). Insomnia was 18 times more likely in the CPTSD group than in the no-PTSD group. There were no differences in insomnia prevalence between the no-PTSD and PTSD groups. Insomnia levels among Yazidi women released from captivity support an understanding of CPTSD as a separate entity than PTSD. Potential factors linking CPTSD to insomnia, beyond those associated with PTSD are discussed.